Tsunamis : detection, monitoring, and early-warning technologies - Joseph, Antony (Academic Press, 2011)
The devastating impacts of tsunamis have received increased focus since the Indian Ocean tsunami of 2004, the most destructive tsunami in over 400 years of recorded history. The tsunamis that occurred as a result of the earthquake in Japan in March 2011 further emphasized the need for detection, monitoring, and early-warning technologies. This professional reference is the first of its kind: it provides a globally inclusive review of the current state of tsunami detection technology and will be a much-needed resource for oceanographers and marine engineers working to upgrade and integrate their tsunami warning systems.